Scaling Roadmap: A Platform for Climate-Smart Feed and Forage Innovations in Ethiopia: DigiFeed360 - Ewell, Hanna; Mekonnen, Kindu; Gebreyes, Million; Makonnen, Brook T.; Ambaw, Gebermedihin; Solomon, Dawit; Girvetz, Evan (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
◼ DigiFeed360 digitizes feed systems, shifting to climate-smart cultivated forages. Bundled advisories, seed systems, and suitability mapping boost productivity, incomes, resilience— advancing equity and stewardship of resources. ◼ Roadmap: 2025–2027 foundations—data sharing, feed-balance tools, calibrated ILRI advisory, seed pilots. 2027–2029 scale—site-specific advisories to 100,000 farmers. Beyond 2030: embedding policies, cooperatives, quality assurance, and inclusive strategies. ◼ Business case: diversify financing— government cost-sharing, seed-enterprise partnerships, DST-informed credit, subscriptions. Strengthen regulation and market linkages; dashboards and feedback via ADPLAC/Dairy enable selfsustaining, climate-smart adoption nationwide.